(untitled) (Eurasian Medical Research Periodical, 2024)
This review presents a modern concept of the factors that contribute to the development of the cardiovascular system. It is noted that local inflammatory reactions in the walls of blood vessels and disruption of lipid metabolism in the course of hypercholesterolemia play an important role in the development of atherosclerosis. The pathogenesis of this condition is multifactorial